Deformations of Pre-Symplectic Structures: a Dirac Geometry Approach - Schätz, F.; Zambon, M. (Symmetry, Integrability and Geometry: Methods and Applications, 2018)
We explain the geometric origin of the L∞-algebra controlling deformations of pre-symplectic structures.